Government policy on the transfer of 3 kilogram lpg subsidies: An analysis of the social and economic impacts in the city of Serang - Hartoko, Gatot; Kamilah, Fithrotul; Priatna, Achmad Nashrudin; Saepudin, Eli Apud (Journal of Law Science, 2025)
This study analyzes the social and economic impacts of the Indonesian government's policy shift regarding the transfer of subsidies for 3-kilogram Liquefied Petroleum Gas (LPG) cylinders.  The policy, aimed at increasing the accuracy and effectiveness of subsidy distribution, introduces a more targeted mechanism to ensure that only eligible low-income households receive assistance. Using a mixed-methods approach that includes qualitative interviews with affected communities and quantitative analysis of household expenditure data, the research reveals several key findings. Socially, the policy change has raised concerns among informal workers and small-scale food vendors, who rely heavily on subsidized LPG for daily operations. The transition process, marked by limited public communication and lack of comprehensive data on beneficiaries, has contributed to confusion and resistance at the grassroots level. Economically, while the policy intends to reduce state budget leakage and promote energy equity, initial findings show an increase in household energy spending among non-registered users and small businesses, potentially affecting their economic resilience. The study concludes that although the subsidy transfer policy has merit in principle, its implementation requires improved targeting systems, stronger data validation, and more inclusive public engagement. Recommendations include the adoption of digital identification systems, real-time monitoring tools, and the gradual integration of renewable energy alternatives to build long-term sustainability and social acceptance.